2020
DOI: 10.31234/osf.io/4nzuy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychological underpinnings of pandemic denial - patterns of disagreement with scientific experts in the German public during the COVID-19 pandemic

Abstract: We investigated laypersons’ agreement with technical claims about the spread of the Sars-CoV-2 virus and with claims about the risk from COVID-19 in the general public in Germany (N = 1,575) and compared these with the evaluations of scientific experts (N = 128). Using Latent Class Analysis, we distinguished four segments in the general public. Two groups (mainstream and cautious, 73%) are generally consistent with scientific experts in their evaluations. Two groups (doubters and deniers, 27%) differ distincti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 66 publications
3
25
1
1
Order By: Relevance
“…However, distrust in science and research, and distrust in political institutions together predicted COVID-19 conspiracy beliefs in Austria more strongly than right-left ideology 91 . Thus, COVID-19 conspiracy beliefs may be predicted by populist attitudes, fuelled by anti-elitism, rather than particular political ideologies 87,91 . In line with this suggestion, COVID-19 conspiracy beliefs have been associated with trust in one's government for countries with populist governments (e.g., Brazil, United Kingdom, United States), but with distrust for countries without these types of governments (e.g., Finland, New Zealand) 15 .…”
Section: Social Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, distrust in science and research, and distrust in political institutions together predicted COVID-19 conspiracy beliefs in Austria more strongly than right-left ideology 91 . Thus, COVID-19 conspiracy beliefs may be predicted by populist attitudes, fuelled by anti-elitism, rather than particular political ideologies 87,91 . In line with this suggestion, COVID-19 conspiracy beliefs have been associated with trust in one's government for countries with populist governments (e.g., Brazil, United Kingdom, United States), but with distrust for countries without these types of governments (e.g., Finland, New Zealand) 15 .…”
Section: Social Factorsmentioning
confidence: 99%
“…Generic beliefs in conspiracy theories (during the COVID-19 pandemic) have, for example, been associated with distrust in the German government, health institutions and healthcare system86 . Believing specific COVID-19 conspiracy theories was associated with doubting or denying technical claims about COVID-19 in Germany87 and was predicted by distrust in scientists in a multinational sample15 . Trust in science predicted adherence to guidelines in Germany88 and in a large international survey (N=23,733) with representative samples from 23 countries89 .…”
mentioning
confidence: 99%
“…Importantly, relying on social media as an information source was not negatively associated with knowledge about COVID-19 (Nielsen et al 2020). Rothmund et al (2020) also showed that being exposed to public broadcasting news was the most important predictor of having knowledge about and evaluations of COVID-19 in line with scientific expert judgements.…”
Section: Covid-19 and Information Exposurementioning
confidence: 76%
“…This situation is aggravated by the fact that many media consumers and users of digital networks are very uncritical and tend to believe in information that confirms their existing beliefs (Rothmund, Farkhari, Azevedo, & Ziemer, 2020;Rosenthal, 2020;Amit Aharon et al, 2020;Peters & Besley, 2020;Rosenthal, 2020;Abdulai et al, 2021;. However, Anwar et al (2020) maintain that "The role of media and public health communications must be understood and explored further as they will be an essential tool for combating COVID-19 and future outbreaks" (p. 1).…”
mentioning
confidence: 99%
“…Naeem and Bhatti (2020) make, in their recent work, a summary of the most common myths that gained strength during the COVID-19 pandemic and that are listed below. This misinformation on COVID-19 may even call into question the scientific studies produced on it (McGinnis, 2020;Al-Zaman, 2020;Rothmund et al, 2020) and permeates social networks and even the media, where journalists should act as gatekeepers, rather than fake-keepers: it in many names: misinformation, disinformation, false news, inaccurate news, and rumor, though the problem remains almost the same. Amid the COVID-19 pandemic, the world is in grief with half a million dead.…”
mentioning
confidence: 99%